Metal Mountable Ladder Feed Line UHF-RFID Tag Antenna - Najwa Mohd Faudzi; Mohd Tarmizi Ali; Ismarani Ismail; Hadi Jumaat; Nur Hidayah Mohd Sukaimi (International Journal of Electrical and Computer Engineering (IJECE), 2015)
A microstrip dipole UHF-RFID tag antenna that can be mounted on metal object is presented in this paper. The antenna, which has a very simple structure without any shorting pin and shorting plate, is composed of ladder feed line, rectangular loop, capacitive tip-loading and T-match structure. The insertion of ground plane in the tag antenna design reduces the negative impact of metal object to the performance of the tag antenna. The tag is designed to operate in the Malaysia frequency range with the center frequency of 921 MHz. The performance of the tag is evaluated through simulation and measurement in terms of impedance matching, antenna reflection coefficient and tag reading range. The measured reading range obtained when the tag is in free air and on metal object is 2.3 m and 2.2 m respectively.